Avaliação do Projeto Estadual de Erradicação do Sub-Registro Civil de Nascimento no Atendimento Materno Infantil no Hospital Geral Dr. César Cals - Luna, Sandra Maria Bezerra (2012)
Access to Civil Registration of Birth gives citizenship and identity, identity of belonging, inclusion, not only with regard to access to public policy, but also how to be right with name, surname and family. Brazil has high underreporting, ie, many children are not civilly registered in the Civil Registry offices until the first 45 days of life. This research aims to assess the general state Eradication Project Sub-birth Records, more specifically identify the interested motives discharge of newborn infants without birth in the civil registry of maternal care - child General Hospital Dr. César Cals, in Fortaleza, but also identify the constraints and potentials of the Service Unit Linked - IU instance created to allow access to the Civil Registration of Birth for all children born in the maternity ward and was discharged with his birth certificate. The research, qualitative analyzes of bibliographic information result, documentary and interviews. The subjects participating in this study correspond to two categories: professionals of that hospital linked to the Service Birth Records and mothers whose deliveries occurred in the unit studied. As results of the fieldwork, when the questionnaires were applied to guide the interviews conducted with these three groups, the case study showed that education, age, marital status, occupation and place of residence are common elements between the mothers interviewed, as well as vulnerability and social risk. Twenty-seven percent reported problems with the recognition of paternity of their children as a justification for not adhering to the services provided by the Hospital to the Civil Registration of Birth. As for the professionals interviewed identified the fact that 42% are social workers, 25% nurses or doctors and 17% allowed scribes. Despite the involvement and commitment of these professionals, there is need for wider dissemination throughout the hospital environment for socialization and access, especially for the case of a hospital that performs prenatal risk.